Advisability of primary intraocular lens implantation for infants under 2: A systematic review and meta‐analysis. Issue 9 (2nd April 2021) - Jin, Shanshan; Zhang, Jingshang; Wang, Jinda; Yusufu, Mayinuer; Cao, Kai; Zhu, Guyu; He, Hailong; Wan, Xiu Hua
Abstract: Purposes: The present meta‐analysis compared the postoperative visual performance of primary intraocular lens (IOL) implantation and primary aphakia in cataract infants. Methods: PubMed, Embase, Science Direct and Cochrane Library were searched, and postoperative visual acuity (VA) and complications were extracted and pooled. Results: Three randomised controlled trails (RCTs) and five retrospective studies were included. The postoperative VA of children younger than 4.5 years in primary IOL group was better than that in primary aphakia group [MD = −0.14, 95% CI: (−0.23, −0.06), P  = .90]. The subgroup analysis based on RCTs and on unilateral cataract surgery revealed the same result. There was no significant difference in the incidence of glaucoma, strabismus, retinal detachment and nystagmus between primary IOL group and primary aphakia group [OR = 1.02, 95% CI: (0.62, 1.68), P  = .48 for glaucoma; OR = 0.76, 95% CI: (0.30, 1.90), P  = .05 for strabismus; OR = 0.49, 95% CI: (0.07, 3.30), P  = .34 for retinal detachment; OR = 1.26, 95% CI: (0.68, 2.36), P  = .92 for nystagmus]. The proportion of patients requiring postoperative visual axis opacification (VAO) clearing was higher in primary IOL group than that in primary aphakia group [OR = 9.22, 95% CI: (4.74, 17.96), P  = .16]. Conclusion: For infants under 2 years of age, primary IOL implantation would provide more visual benefits compared with primary aphakia did, though the benefits would taper off with the age reaching 4.5 years. Moreover, the current study revealed a higher VAO incidence r in primary IOL implantation group.